Prasangka Etnis dan Ujaran Kebencian: Analisis Ujaran Kebencian terhadap Etnis Tionghoa di Twitter (X) - Priyatna, Adry Alim; Wibowo, Kunto Adi; Syafirah, Nuryah Asri (Jurnal Komunikasi, 2024)
This study aims to determine the meaning of the text of hate speech targeting ethnic Chinese in Indonesia on Twitter social media. In addition, it also aims to reveal the social cognition and social context of the discourse surrounding the phenomenon of hate speech to Chinese ethnic. This study uses a qualitative method in the form of text analysis with a critical discourse analysis approach of Van Dijk's model. The research findings show that the macrostructure of the hate speech text has a certain theme and Twitter citizens have their definition of the word "China" as social cognition. The developing social context is issues related to government policies, namely the development of the capital city of the Archipelago and the polarization of society after the 2019 presidential election, which are collected in the form of discourses of disliking President Jokowi's government